Calcium Silicate-Based Root Canal Sealers: A Narrative Review and Clinical Perspectives - Sfeir, Germain (Materials (Basel), 2021)
Over the last two decades, calcium silicate-based materials have grown in popularity. As root canal sealers, these formulations have been extensively investigated and compared with conventional sealers, such as zinc oxide–eugenol and epoxy resin-based sealers, in in vitro studies that showed their promising properties, especially their biocompatibility, antimicrobial properties, and certain bioactivity. However, the consequence of their higher solubility is a matter of debate and still needs to be clarified, because it may affect their long-term sealing ability. Unlike conventional sealers, those sealers are hydraulic, and their setting is conditioned by the presence of humidity. Current evidence reveals that the properties of calcium silicate-based sealers vary depending on their formulation. To date, only a few short-term investigations addressed the clinical outcome of calcium silicate-based root canal sealers. Their use has been showed to be mainly based on practitioners’ clinical habits rather than manufacturers’ recommendations or available evidence. However, their particular behavior implies modifications of the clinical protocol used for conventional sealers. This narrative review aimed to discuss the properties of calcium silicate-based sealers and their clinical implications, and to propose rational indications for these sealers based on the current knowledge.